The polyps of Oceania armata identified by DNA barcoding (Cnidaria, Hydrozoa) - Schuchert, Peter (Zootaxa, 2016)
The polyps of the widely distributed medusa Oceania armata have never been found in nature and only the primary polyp is known from breeding experiments. The fully developed colony is so far unknown. This report shows that DNA sequence data of the medusa stage of O. armata permits to identify several hydroid colonies from different geographic origins as the most likely polyp stage of this medusa. These hydroids had previously been misidentified as Turritopsis species, a closely related genus which also produces medusae resembling Oceania armata. It is concluded that most Turritopsis hydroids are not reliably identifiable to species level using morphological traits only. However, DNA barcodes, particularly 16S sequences, are an excellent tool to identify the species, although we still lack information on a few nominal species and the identities of some sequence-delimited clades need to be corroborated by the addition of topotype samples.